New methodologies for second language assessment: measuring and identifying profiles in migrant school contexts - Figueiredo, Sandra (2018)
In Education, the policy related to immigrant school population is of upmost importance considering the migratory history and the current scenarios of Multilingual classrooms. The research evidence in second language area is a very recent period in science, mainly regarding the assessment concerns and responsiveness. To be inclusive, school professionals needs differentiated tools to assess and place students. The diagnostic evaluation is the first step in educational scientific research, in this field. On one hand, the language assessment in second language context is still a gap in portuguese schools and at research settings; on the other hand, the international scientific research still presents contradictory frameworks regarding standardization of norms and benchmarks to develop tests and scoring. In this work new methodologies are addressed as instrument for school improvement, specifically regarding second language learners. Our research is focused in the development of a diagnostic test to assess proficiency and skills of students in Portuguese language, creating validated measuring and reliable training in this area. Literacy practitioners should be aware of profiles and needs of immigrant students, so far this was not achieved in our national system using oversampling in research studies. Particularly here we will provide an examination of the type of responses that Portuguese language learners present in such second language diagnostic tests, integrating several tasks to ensure enough observations and reliable scores, to determine profiles that inform how to score constructed-response items. This research will be able to describe the type of responses and specific language errors that would be useful as training clues (as rubrics for each content area) to define correct language and grammar to be expected to receive positive scores in the test. Teachers and students are still unfamiliar with these tests and the orientation about fulfilment and scores should be supported by research results and validated material to help to apply specific evaluation to specific responses, in real school contexts.